Etymological Characteristics of the Term «Mythologeme» - Nazarova, А.; Mansurov, Н. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2019)
Currently, at the stage of formation and development of the mankind, the study of its culture, customs and traditions, national characteristics is important. Improvement of human consciousness in understanding the environment has become a social value in social and cultural life. The culture of any ethnic group is manifested through the myth. In a whole, the world in human development exists in mythical legends kept for thousands of years in the knowledge of the world and the universe. The article deals with a significant concept –“mythologeme”, in which the usage of this term is associated with the psychologist K.G.Jung. In the study the etymological significance of this term is considered. The main concept of the study is that the statements of researchers and definitions in terminological dictionaries were taken into account. The term «mythologeme» preserved in national memory of any ethnic group and manifested in the culture of each nation is described. During the analysis of the work, the definitions of the term had been systematized